SARS‐CoV‐2 and pregnancy outcomes under universal and non‐universal testing in Sweden: register‐based nationwide cohort study. (18th November 2021) - Stephansson, O; Pasternak, B; Ahlberg, M; Hervius Askling, H; Aronsson, B; Appelqvist, E; Jonsson, J; Sengpiel, V; Söderling, J; Norman, M; Ludvigsson, JF; Neovius, M
Abstract : Objective: To assess associations of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and pregnancy outcomes considering testing policy and test‐positivity‐to‐delivery interval. Design: Nationwide cohort study. Setting: Sweden. Population: From the Pregnancy‐Register we identified 88 593 singleton births, 11 March 2020–31 January 2021, linked to data on SARS‐CoV‐2‐positivity from the Public Health Agency, and information on neonatal care admission from the Neonatal Quality Register. Adjusted odds ratios (aORs) were estimated stratified by testing‐policy and test‐positivity‐to‐delivery interval. Main outcome measures: Five‐minute Apgar score, neonatal care admission, stillbirth and preterm birth. Results: During pregnancy, SARS‐CoV‐2 test‐positivity was 5.4% (794/14 665) under universal testing and 1.9% (1402/73 928) under non‐universal testing. There were generally lower risks associated with SARS‐CoV‐2 under universal than non‐universal testing. In women testing positive >10 days from delivery, generally no significant differences in risk were observed under either testing policy. Neonatal care admission was more common (15.3% versus 8.0%; aOR 2.24, 95% CI 1.62–3.11) in women testing positive ≤10 days before delivery under universal testing. There was no significant association with 5‐minute Apgar score below 7 (1.0% versus 1.7%; aOR 0.64, 95% CI 0.24–1.72) or stillbirth (0.3% versus 0.4%; aOR 0.72, 95% CI 0.10–5.20). Compared with term births (2.1%), test‐positivity was higher in medically indicated preterm birth (5.7%; aOR 2.70, 95% CI 1.60–4.58) but not significantly increased in spontaneous preterm birth (2.3%; aOR 1.12, 95% CI 0.62–2.02). Conclusions: Testing policy and timing of test‐positivity impact associations between SARS‐CoV‐2‐positivity and pregnancy outcomes. Under non‐universal testing, women with complications near delivery are more likely to be tested than women without complications, thereby inflating any association with adverse pregnancy outcomes compared with findings under universal testing. Tweetable abstract: Testing policy and time from SARS‐CoV‐2 infection to delivery influence the association with pregnancy outcomes. Tweetable abstract: Testing policy and time from SARS‐CoV‐2 infection to delivery influence the association with pregnancy outcomes.